Cameras on beds: The ethics of surveillance in nursing home rooms. Issue 1 (2nd January 2019) - Berridge, Clara; Halpern, Jodi; Levy, Karen
Abstract: Surveillance cameras are increasingly being deployed in nursing homes and assisted living facilities, with insufficient attention to what is ethically fraught about this way of assuaging concerns about abuse and other personnel challenges. With seven state laws now regulating camera monitoring and more on the way, it is urgent for us to consider the ethical implications of how we use technology to keep older adults safe. Drawing on findings from the first facility survey on this topic, we address three ethical issues: the risk that in-room cameras pose to residents' privacy and dignity, the risk of undermining care workers' sense of being fiduciaries for residents, and the probable extension of camera use by facilities to monitor staff and residents. We argue that with an aging population, intensifying strain on the care workforce, and ease of access to Web-connected cameras, this is a critical moment to address these ethical challenges.